ChemInform Abstract: Poly(N‐isopropylacrylamide) Phase Diagrams: Fifty Years of Research. Issue 8 (February 2016) - Halperin, Avraham; Kroeger, Martin; Winnik, Francoise M.
Abstract: Review: [59 refs.